Inhibitory effects of the JAK inhibitor CP690,550 on human CD4(+ )T lymphocyte cytokine production - Migita, Kiyoshi (BioMed Central, 2011)
BACKGROUND: The new JAK3 inhibitor, CP690,550, has shown efficacy in the treatment of rheumatoid arthritis. The present study was undertaken to assess the effects of CP690,550 on cytokine production and cellular signaling in human CD4(+ )T cells. RESULTS: CD4(+ )T cells produced IL-2, IL-4, IL-17, IL-22 and IFN-γ in following stimulation with a CD3 antibody. At the optimal concentration, CP690,550 almost completely inhibited the production of IL-4, IL-17, IL-22 and IFN-γ from these activated CD4(+ )T cells, but only had marginal effects on IL-2 production. Moreover CP690,550 inhibited anti-CD3-induced phosphorylation of STAT1, STAT3, STAT4, STAT5, and STAT6, but not the TCR-associated phosphorylation of ZAP-70. CONCLUSIONS: Therefore, CP690,550-mediated modification of the JAK/STAT pathway may be a new immunosuppressive strategy in the treatment of autoimmune diseases.